The frequency of gestational diabetes mellitus among pregnant mothers admitted in gynaecology/obstetrics ward of Sheikh Zayed Hospital Rahim Yar Khan, Pakistan - Faisal, Muhammad; Bakar, Muhammad Abu; Hussain, Zahid; Abbas, Khizer (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: The gestational diabetes mellitus (GDM), defined as my degree of glucose intolerance with onset of first recognition during pregnancy, is poorly understood due to low socioeconomic dynamics among the pregnant mothers of Rahim Yar Khan. It results in many maternal and fetal complications. This study was carried out to determine the frequency and socio- demographic profile of pregnant mothers with gestational diabetes mellitus admitted in Gynecological Obstetrics wards of Sheikh Zayed Medical College Hospital Rahim Yar Khan. Methods: The data for this cross-sectional study was collected during the period from 30-01-2017 to 30-06-2017. The data was collected from labor room and wards of gynecology Sheikh Zayed Hospital Rahim Yar Khan. This study was conducted among the 160 pregnant mothers in Labor room and gynecological wards of Sheikh Zayed Hospital Rahim Yar Khan, admitted during the study period. A predesigned questionnaire was filled by interviewing these mother shaving variables of age, education, residence, working status, BMI, family monthly income, total numbers of children, knowledge of Gestational diabetes mellitus and family history of GDM. Results: The frequency of GDM in this study was significantly associated with reproductive age group 25-34 years (64%), Illiteracy in mothers (53.8 %) from rural area (>50%) housewives (83%), BMI (Mean = 22), Family Monthly income (> 10,000 Rs.), Average no. of Children (2-3), Diagnosed with Gestational Diabetes Mellitus (15.6%), Family history of D.M (>50%). Conclusions: It is concluded that the frequency of Gestational Diabetes Mellitus was high. Early detection, constant sup0ervision, delivery with intensive intra-partum monitoring, facilities of expert neonatologists, proper health care education to pregnant mothers can result in good maternal and fetal outcomes without much morbidity.